(untitled) (American Journal of Agricultural Science, Engineering, and Technology, 2023)
The impact of aqueous extracts from the leaves of Callistemon rigidus, Lippia multiflora and Plectranthus glandulosus on the foraging behavior of Apis mellifera on Glycine max flowers were evaluated in Ngaoundéré Cameroon, during two successive agricultural seasons. The search was conducted in 1064 m2 experimental field with treatments arranged in a completely randomized blocks design 4 times replicated: 1 control x 3 plants x 3 extracts x 3 concentrations (5%, 10% and 15%) x 1 standard synthesis insecticide (Decis) x four groups of flower buds (group 1: flowers free to insect visits; group 2: flowers protected from insects using gauze bags; group 3: protected flowers and opened exclusively to A. mellifera and group 4: protected flowers opened from time to time without any visit of insects or other organisms). This Fabaceae was visited by nine species of insects of which the honeybee, A. mellifera was the most numerous (> 90%) and exclusively collected nectar. The different insecticides tested were attractive to this pollinating insect, specially at the concentration of 15%. The mean duration visit of this bee varied from 1.9 sec on the plots treated with Decis to 4.4 sec on the plots treated with 15% C. rigidus. The fruiting indices were 0.96, 0.69, 0.94 and 0.67 respectively for flowers of group 1, 2, 3 and 4. Callistemon rigidus at the content of 15% significantly improved the fruiting rate compared to the other treatments. According to this study, it would be wise to use aqueous extracts at 15% concentrations to improve the pollinating activity of A. mellifera in order to improve seed yield.